An Analysis of Movement and Performance In 3D Animation: Exploring the Kinesic Performance in 3D Animation (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In animation the issue of movement is central to any discussion of its nature, irrespective of its form,  style or  process  of  creation.  As  an  animator, Norman  McLaren believed “the most important  thing in film is motion,  movement” (in Benghazi, 1994:117), whilst Wells describes animated  films as “the  artificial creation of the  illusion of movement  in inanimate  lines and forms” (1998:10). Movement is of primary concern in this simple definition and in earlier critical analyses of  animation,  Sergei Eisenstein “ recognised  ‘if it  moves, then  it’s  alive’”  [italics in original]  (Leyda,  1988:54  quoted in Wells, 1998:14). This  paper  considers  the  concept of movement in animation films expressed in the kine sic performance of the character(s).